Gaps in the Management of Type 2 Diabetic Patients in a Metropolitan Area of Havana - Armando Rodríguez Salvá; Linet Céspedes Hernández; Addys Díaz Piñera; René García Roche; Susana Balcindes Acosta (Universidad de las Ciencias Médicas de Cienfuegos, 2019)
Foundation: there are flaws in diabetic patient management this makes it difficult to develop intervention strategies to improve the quality of their medical care. Objective: to identify the main gaps which affected the comprehensive management of diabetic people, in a metropolitan area of Havana during 2016. Methods: a cross-sectional descriptive investigation was carried out. Sample selection was made by bi periodic conglomerate sampling, it consisted of 580 people, to whom an instrument made for this purpose was applied. Number variables were presented with central tendency and dispersion measures. Categorical variables were shown as frequencies and percentages. Results: 96.4 % of the interviewees needed medical attention in the last year. Out of them, 90.5 % attended primary health care. There were difficulties with attention due to organizational problems and lack of resources, although 85 % of the patients were satisfied with the received care. The main gap was follow-up, with only 69.7 % of the patients consulted in the last year. 68.3 % have indicated pharmacological treatment, and of these 77.5 % is adhered to according to the Morinsky test 83.4 % had their blood glucose levels checked. Conclusions: gaps related to health services access are a direct consequence of the instability of health personnel. This affects the patient control due to noncompliance in the schedule and periodicity of follow-up medical consultations.